Start of Higher School in Crimea: Taurida University (1918-1920) - Sergey B. Filimonov (Moscow Polytechnic University, 2019)
October 14, 2018 marked the 100th anniversary of the inauguration of the first university in Crimea, which initially, in 1918-1920, was called the Taurida University, and now is V.I. Vernadsky Crimean Federal University. In this regard, it is useful to recall the main stages of the history of the university. Of particular interest is the history of Taurida University in the years of the Civil War, when its teachers were the greatest scientists who fled from the Bolshevik terror from the university centers of the former Russian Empire to the "white" Crimea. But it was precisely this period that received the least coverage in the literature published in the twentieth century. The main reason for this is the lack of a sufficient source base. After all, the pre-war university archive was lost, and the main source for a long time remained only two volumes of the "News of the Tauride University" published in 1919 and 1920. The noted narrowness of the source base forced researchers to look for additional sources of information. Attention was drawn to the archives of institutions, organizations and individuals associated with the university in the initial period of its existence, as well as sources of personal origin (diaries of Academician V.I. Vernadsky, memories of his son, Professor G.V. Vernadsky, etc.).In the late 1990s, the author of the article was fortunate enough to reach the richest unique source that remained untapped by researchers on the history of the Crimean intelligentsia, science and culture in 1917-1920 - Crimean newspapers during the Civil War. On their pages, it was possible to find not only chronicle notes to recreate the missing pages of the history of Taurida University and existing scientific societies, not only information about the participation of university professors in the activities of numerous Crimean scientific organizations, but also publications of a number of leading scientists that remained unknown.The present article is based mainly on these newspapers, which have long become a bibliographic rarity.